Waves : examining interactions - Vink, Amanda (Spotlight on physical science., 2020)
Examines the history and evolution of how waves are studied and manipulated and why continued study is important. Includes illustrations and photographs, sidebars, a glossary, a primary source list, sources for further information, and an index.